2014
DOI: 10.1111/jhn.12225
|View full text |Cite
|
Sign up to set email alerts
|

Food frequency questionnaire as an indicator of the serum composition of essential n‐3 and n‐6 polyunsaturated fatty acids in early pregnancy, according to body mass index

Abstract: FFQ in early pregnancy may be used as a possible indicator of serum concentrations of fatty acids. Higher correlations were observed among underweight/normal weight women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…39% of women in the cohort did not report intake of fresh fish, and 34% reported intake once a month. Overall, the median dietary intake of EPA and DHA was 0.025 g (interquartile range = 0.01–0.03) per day and 0.026 g (interquartile range = 0.0–0.03) per day [45] respectively, which was far bellow the recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39% of women in the cohort did not report intake of fresh fish, and 34% reported intake once a month. Overall, the median dietary intake of EPA and DHA was 0.025 g (interquartile range = 0.01–0.03) per day and 0.026 g (interquartile range = 0.0–0.03) per day [45] respectively, which was far bellow the recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of fatty acids are known as biological markers of dietary intake in epidemiological investigation [39]. The serum composition of essential n-6 and n-3 fatty acids assessed in the first trimester (cohort baseline) partially reflects the usual diet with less interference of the gestational period [45]. A further strength is the use of different instruments, including a validated scale (EPDS) to measure depressive symptoms and a structured interview to assess the diagnosis of major depressive episodes (MINI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have previously demonstrated that this FFQ may be used as a possible indicator of serum concentrations of n‐3 FA in early pregnancy (Lepsch et al . , ). In contrast, the longitudinal design with repeated measures and the availability of serum concentrations of FA at three time points are the main strengths of this study.…”
Section: Discussionmentioning
confidence: 97%
“…Our results showed that greater adherence to the common‐Brazilian DP was associated with a slight increase in total n‐3 serum content in normal and obese pregnant women. Fresh meat and eggs, which are alternative sources of n‐3 PUFA (Lepsch et al, ), are food items found in the common‐Brazilian DP and, therefore, could have contributed to the positive impact on n‐3 FA. On the basis of the reduced rank regression analysis, Pounis et al () identified that the DP that most explained the variations in n‐3 PUFA in plasma included food items not considered as main sources of n‐3 PUFA, such as cabbages and root vegetables, dairies, vegetable oils, chocolate, coffee and tea, and mayonnaise, which is in accordance with our results regarding the common‐Brazilian DP.…”
Section: Discussionmentioning
confidence: 99%